2011
DOI: 10.4103/0972-0707.87215
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of microleakage of class II packable composite resin restorations using flowable composite and resin modified glass ionomers as intermediate layers

Abstract: Aim and Objectives:To evaluate the cervical marginal microleakage of class II packable composite resin restorations using flowable composite and resin modified glass ionomer as intermediate layers and whether the difference in the thickness of these intermediate layers would influence the microleakage.Materials and Methods:Standardized class II box only cavities (4 mm bucco lingual width 2 mm mesio distal depth with the gingival margin 1 mm above the cemento-enamel junction (CEJ) were restored as follows: Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 4 publications
2
25
0
3
Order By: Relevance
“…The integrity of the marginal seal is essential to increase the longevity of the restoration [16]. That integrityis compromised when microleakage occurs resulting from polymerization shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…The integrity of the marginal seal is essential to increase the longevity of the restoration [16]. That integrityis compromised when microleakage occurs resulting from polymerization shrinkage.…”
Section: Discussionmentioning
confidence: 99%
“…Teniendo en cuenta los factores antes mencionados, para evitar al máximo la infiltración marginal, un material restaurador debe presentar una excelente adaptación, mínima contracción de polimerización y un módulo de elasticidad lo suficientemente bajo como para compensar la tensión generada en la interfase (5), obteniéndose así un sellado marginal, el cual es esencial en cualquier sistema restaurador para mantener la vitalidad pulpar y aumentar la longevidad de la restauración (14). Una vez polimerizado, el material debe sufrir un desgaste mínimo en el tiempo y poseer una estabilidad dimensional térmica similar a los tejidos dentarios, ya que una gran diferencia en el coeficiente lineal de expansión térmica entre el diente y el material restaurador puede producir microfiltración en los márgenes de la restauración (30).…”
Section: Discussionunclassified
“…Sin embargo, también poseen inconvenientes como los relacionados a la generación del punto de contacto (11) y el desarrollo de estrés en la interfase diente-restauración durante la polimerización (12). Para reducir estos efectos se ha recomendado el uso de resinas compuestas fluidas como liner bajo resinas condensables en el margen gingival de cajas proximales en restauraciones clase II, para mejorar así la integridad marginal (13,14) con resultados aún discutibles (15,16).…”
Section: Introductionunclassified
“…[22232425] Majety and Pujar[26] reported that the thickness of the flowable composite intermediate layer does not affect micro-leakage. Swift et al .…”
Section: Discussionmentioning
confidence: 99%